ANALISIS MULTI-STAKEHOLDER PARTNERSHIP DALAM PENGURANGAN DEFORESTASI LAHAN GAMBUT DI KALIMANTAN TENGAH TAHUN 2017-2020 - Putra, Marcerio Britama; Suryo Sakti Hadiwijoyo; Hergianasari, Putri (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2022)
This study aims to determine efforts to reduce deforestation on peatlands in Central Kalimantan through the formation of the Peat Restoration Agency in 2016 by President Joko Widodo. Based on the BRG program, cooperation from various stakeholders is needed, such as regional officials through the Regional Peat Restoration Team, International Institutions, and Community Groups to maximize activities in efforts to reduce peatland deforestation. With an analysis of liberalism institutional theory and the method used is descriptive qualitative by collecting data through interviews and related documents. This restoration program was carried out in the first phase for 5 years from 2016-2020 through the 3R program (Rewetting, Revegetation, Revitalization) which focused on 705,458 hectares of burnt areas in 2015-2019. Over time, significant progress has been shown in reducing peatland deforestation in Central Kalimantan, which involves many stakeholders by prioritizing contributions from the community. The results of this study indicate that in 2015-2017 there was deforestation of 228,954.26 hectares which was significantly reduced to 6,926.10 hectares in 2019-2020.